Geoeffectiveness of stream interaction regions during 2007–2008. Issue 8 (29th August 2017) - Sanchez‐Garcia, E.; Aguilar‐Rodriguez, E.; Ontiveros, V.; Gonzalez‐Esparza, J. A.
Abstract: The stream interaction regions (SIRs) are generated in the interplanetary medium when a fast solar wind stream overtakes a slower one. If these large‐scale phenomena interact with the Earth's magnetosphere, they can give rise to geomagnetic storms (GSs). Their geoeffectivity is measured using magnetic indices at different latitudes. In this study we analyzed the geoeffectiveness of 20 GSs that were generated by SIRs during the period of 2007 to 2008 and observed by the ACE, Wind, and STEREO‐A/B spacecraft. We compared the geomagnetic response to the SIRs‐magnetosphere interaction employing different geomagnetic indices at low, middle, and high latitudes. The geoeffectiveness was 50%, 55%, and 90% using the criteria of the a a, K p, and S Y M ‐ H indices, respectively. We found that in most cases the maximum intensity of each index was in the weak to moderate range. According to the S Y M ‐ H index, a 10%, 60%, and 10% of the forward shocks were followed by quiet, weak, and moderate GSs, respectively. The 10% and 20%, however, were followed by minor and moderate GSs, respectively, according to the K p index. We analyzed the geoeffective region within the SIRs with respect to the relative position of the stream interface (SI). For 75% of GSs, their maximum intensity occurred during the disturbed fast solar wind (after the passing of the SI), which would be related to the efficiency of a SIR. The time difference Δ t between the passing of the SI and the maximum intensity in each index was less than 36 h. Key Points: Analyze the stream interaction regions in their arrival to our magnetosphere Measure of the geoeffectiveness that were generated by the stream interaction regions by using different magnetic activity indices Survey the geoeffective region within the SIR with respect to the relative position of the stream interface